Evaluation of Psychoanalytic Oriented Psychotherapy Outcome Using Rorschach and TAT: A Case Study - Zihniye OKRAY (Yaşam Becerileri Psikoloji Dergisi, 2017)
Projective techniques especially Rorschach and TAT ( Thematic Apperception Test) have a wide variety of assestment areas. These techniques have been used from selection of staff for a appropriate job, giving diagnosis to psychiatric patients, in child services for counseling, selection and evaluation of military personel. Apart from these uses they also have valuable contributions to the efficiency of a certain treatment programs with helping clinicans to evaluate the psychodynamic properties of a client to decide the type, duration and specific issues in the treatment programme (Deabler, 1947, Weiner, 1997, Tunaboylu-İkiz, 2001, 2002, 2010,2011, Anzieu & Chabert, 2011). In this study a case who was treated with psychodynamic oriented psychotherapy for 2 years the outcome of the threapy evaluated with Rorschach and TAT. In the first assestment before the psychothreapy began the Detail responses given by the patient was to much inorder to protect himself from the dangers coming from the real world.The content of the responses also showed the same charasteristic with using the same theme all over the full protocol.Case’s problems around his self-representaion, self, identification- differences between gender and object relations was evaluated with TAT that showed object loss was the main problematic. After 2 years with the termination of the threapy the second evaluation was done. In this second evaluation the case led himself more freely to the test material with less resistance. In the second evaluation; the case’s cognitive processes and using of words are more rich wch represents high cognitive and entellectual capacities. He is less resistant to unconscious material, sexual contents coming up in responses with more intellectual ways. With these two assestment the efficiency of psychodynamic oriented psychothreapy was proved. Although the case’s perception of the real world still contains some aspects of threads the second evaluation showed that he is more open to his drives. Also ın the second evaluation the main problematic issues upon self-representaion, self, identification- differences between gender and object relations were in normalized matter